A comprehensive study of project risks in road transportation networks under CPEC - Sajjad Alam; Zhijun Yin; Ahmad Ali; Sikander Ali; Abdul Noor; Nadeem Jan (International Journal of Financial Studies, 2019)
The China-Pakistan economic corridor (CPEC) is a collection of different ongoing projects including transportation, infrastructure, the Gwadar seaport, oil pipeline, and internet connection zone projects. The Chinese government has adopted a development strategy for infrastructure growth and investment in Pakistani and Asian territories through the CPEC project. Transportation is considered the backbone of the CPEC. In addition to the CPEC project is the linked 'belt and road initiative' (BRI) project, which aims to enhance regional connectivity and is a harbinger of the future in Asia, as well as in European countries. However, uncertain situations, such as a lack of proper planning, security, and political stability, hinder the growth and development of infrastructure. Three corridors of the CPEC road transportation network, namely, the eastern, the western, and future central alignment, have been examined through a master supposition group using the Delphi technique, which has never been applied to the road transportation network in the CPEC plan. The review is designed to draw master conclusions and demonstrate an outcome for round one and two in the present work. Round one and two investigate the impact of stakeholder support, politicians' roles, terrorism, security situations, poverty, and economic crises. Using the Delphi technique within the host country hinders the construction of the road network. The results obtained through the appraisal have justified the present potential endeavor.
Keywords: 330; China-Pakistan economic corridor (CPEC); Delphi technique; project risk; road transportation network; belt and road initiative (BRI)